Uncitral Model Law on Electronic Transferable Records: Is It an Applicable Legal Framework for Bills of Lading Under Turkish Law? - Ayşe Nilay Şenol; Işık Özer; Gülfer Meriç (Annales de la Faculté de Droit d’Istanbul)
The purpose of the “Model Law on Electronic Transferable Records” adopted by UNCITRAL on July 13, 2017, is to provide a legal framework for the digitisation of paper-based transferable documents or instruments. For this purpose, it is recognised that “functional equivalence” must be achieved between a paper-based document and an electronic record. The law also adopts the principle of “technological independence”. In accordance with this principle, the law does not recommend or endorse the use of a particular technology, method or product for electronic transactions. Similarly, the choice of paper-based documents covered by the law is left to national law. The important thing is that the document is transferable. However, UNCITRAL states that the use of electronic bills of lading in particular, should be facilitated because of its importance in maritime trade among transferable documents. It is also important for our country to adopt the MLETR to ensure international harmonisation and the development of international trade. For this reason, this study analyses whether the bill of lading qualifies as an electronic transferable record, as stipulated in the MLETR under Turkish law. In this context, it is explained whether the conditions of writing, signature, transferability, and control can be achieved in an electronic environment.